Association of preoperative controlling nutritional status score with clinical outcomes among surgical patients with esophageal cancer: a meta-analysis - Ji, Yanli; Wang, Lei; Mei, Xiaoli; Zheng, E; Lin, Lin; Yang, Mei (Frontiers in Oncology, 2025)
PurposeThe aim of this study was to identify the relationship between preoperative controlling nutritional status (CONUT) score and long-term and short-term outcomes in patients with esophageal cancer receiving esophagectomy.MethodsThe Web of Science, EMBASE, PubMed, and CNKI databases were searched up to 24 January 2025. Primary outcome was long-term survival such as the overall survival (OS), disease-free survival (DFS), and cancer-specific survival (CSS). Secondary outcomes included the postoperative overall complication, incision infection, anastomotic fistula, pneumonia, respiratory complication, 90-day death, cardiovascular complication, major adverse cerebrocardiovascular event (MACCE), pulmonary atelectasis, and pulmonary embolism. Hazard ratio (HR) and odds ratio (OR) with 95% confidence interval (CI) were separately combined for the primary and secondary outcomes. Subgroup analysis for the OS and DFS by neoadjuvant therapy and pathological type was further conducted.ResultsEighteen studies with 5,495 cases were included. Pooled results manifested that elevated preoperative CONUT score predicted significantly worse OS (HR = 1.75, 95% CI: 1.30–2.37, p<0.001), DFS (HR=1.21, 95% CI: 1.13–1.30, p < 0.001), and CSS (HR = 2.60, 95% CI: 1.65–4.10, p<0.001). Subgroup analysis for the OS and DFS by the history of neoadjuvant therapy and pathological type demonstrated similar results. Furthermore, elevated CONUT score was significantly related to increased risk of overall complication (OR = 1.50, 95% CI: 1.14–1.96, p=0.004), pneumonia (OR= 1.60, 95% CI: 1.23–2.08, p<0.001), respiratory complication (OR = 1.60, 95% CI: 1.26–2.03, p<0.001), cardiovascular complication (OR = 3.660, 95% CI: 1.068–12.550, p=0.039), MACCE (OR = 1.920, 95% CI: 1.068–3.452, p=0.040), and pulmonary atelectasis (OR = 2.314, 95% CI: 1.408–3.805, p<0.001).ConclusionPreoperative CONUT score might serve as a prognostic indicator in surgical esophageal cancer, and patients with elevated CONUT score are suggested to experience worse long-term and short-term clinical outcomes.